Transfer and mobility of higher education policies in Latin America in neoliberal times - Hostins, Regina Célia Linhares; Hoepers, Idorlene da Silva (Education Policy Analysis Archives, 2017)
Abstract: The paper aims to trace the flows of global education policies in Higher Education policies in two Latin American countries - Brazil and Argentina – during the decades of 1990 and 2000, from Stephen Ball’s theoretical and methodological framework. Two major events were used for analysis - the World Conference on Education for All (Jomtien, 1990), and the World Education Forum (Dakar 2000), which are references in the transfer movement and transnational mobility of education policies led by international agencies such as the World Bank and The United Nations Organization for Education, Science and Culture (UNESCO), among others. These events and resulting documents inaugurated the discursive and epistemic connectivity of global policy networks and the export/import of reform speeches (Ball, 2014), in an environment conducive to the flow of ideas, people and values. As a result, concepts, set priorities and ratified agendas of transnational actions were disseminated, in which the Latin American countries had significant participation and established consensus on Education Reform. Within Higher Education in countries like Brazil and Argentina, a strong expression of the concepts and recommendations of the documents signed at these events was observed during this period. Thus, this paper highlights the recommendations incorporated in some policies of these countries and the interpretation of movements in the context of national policies, taking into account the historical context and political networks established in each country.